2018
DOI: 10.3892/ol.2018.8223
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus inhibits the expression of complement C3 and C4, in�vitro and in�vivo

Abstract: Abstract. The immune system serves an important function in Hepatitis B virus (HBV) infection, and the complement system is a major component of innate immunity. However, the regulatory effect of HBV on complement proteins has not yet been fully elucidated. The present study focused on investigating the impact of HBV on the expression of complement proteins C3 and C4. A total of 226 patients with a clinical diagnosis of HBV infection were enrolled in the study, including 153 with chronic hepatitis B (CHB) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Besides, multivariate Cox regression analysis also showed that C3 levels are an independent predictor of mortality of HBV‐ACLF patients 31 . Similarly, Zhu et al also found that levels of C3 and C4 of CHB patients were significantly lower than those of healthy controls and Huh7 cells transfected with pHBV1.3 displayed lower C3 and C4 expression 32 . Gai et al reported that serum levels of C3 and C4 were significantly higher in patients with HBV‑related compensated cirrhosis compared to decompensated cirrhosis and treatment with entecavir could increase C3 and C4 expression 33 .…”
Section: Discussionmentioning
confidence: 86%
“…Besides, multivariate Cox regression analysis also showed that C3 levels are an independent predictor of mortality of HBV‐ACLF patients 31 . Similarly, Zhu et al also found that levels of C3 and C4 of CHB patients were significantly lower than those of healthy controls and Huh7 cells transfected with pHBV1.3 displayed lower C3 and C4 expression 32 . Gai et al reported that serum levels of C3 and C4 were significantly higher in patients with HBV‑related compensated cirrhosis compared to decompensated cirrhosis and treatment with entecavir could increase C3 and C4 expression 33 .…”
Section: Discussionmentioning
confidence: 86%
“…Liver function impairment would not only lead to the decreased expression of C3 and C4, 16 but also result in lower synthesis of anti-coagulation factors, including plasma protein C, protein S, and antithrombin-III. Furthermore, splenectomy itself would lead to a loss of splenic filtering function and result in the accumulation of abnormal erythrocytes in circulation, thus potentially exposing phosphatidylserine on cell surfaces and activating coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Cleaved complement C3 triggers activation of the complement cascade, which augments host immune functions including lysis of bacteria and cells by forming membrane‐attack complex, opsonization, and chemotaxis of leukocytes . It is not surprising that downregulation of complement C3 was detected in patients with HCC because of their compromised immune system during hepatocarcinogenesis. However, beyond empirical speculation, we found that the level of complement C3 correlated positively with poor differentiation of tumor cells and an unfavorable prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%